ANALISA KONDISI STRUKTURAL PADA JALAN BERDASARKAN HUBUNGAN ANTARA KETIDAKRATAAN PERMUKAAN JALAN (IRI) DAN INDEKS KONDISI JALAN (RCI) (SP –KERKAP – BATAS SUMBAR ) - kadibengkulu kadi; james Hellyward (Universitas Bengkulu, 2024)
Road surface smoothness measurements are not widely conducted in Indonesia due to limited equipment, resulting in inadequate monitoring and evaluation of existing road constructions according to national road sector standards. Road surface smoothness levels can be determined by measurements using various methods recommended by Bina Marga and AASHTO. One method recommended by Bina Marga for measuring road smoothness levels is through road damage survey forms according to the 2015 road condition reporting guidelines. The average road damage level for the Sp.Kerkap–Batas Sumber Road Section is 5.130%. The location Km.Bdg. 63+000-64+000 has the highest IRI value of 12, dominated by damage such as shallow potholes covering an area of ​​8,916.56m², which is planned to be repaired using hotmix patching. Therefore, road observers must be vigilant and regularly report road damages every month to ensure the stability and condition of the road are well maintained, in order to facilitate and support economic flow/velocity. Proper and appropriate handling will keep the road in good condition based on the planned road stability.